h + k - 2k + h

5 answers

By combining like terms, h + k - 2k + h simplifies to:

2h - k
(p -3) - (2.4 + 2p)
To simplify the expression (p - 3) - (2.4 + 2p), we distribute the negative sign to the terms inside the second parentheses:

= (p - 3) - 2.4 - 2p

Next, we can combine like terms:

= p - 2.4 - 2p - 3

Rearranging the terms:

= (p - 2p) - 2.4 - 3

= -p - 2.4 - 3

= -p - 5.4
1(p -3) - 1(2.4 + 2p)
To simplify the expression 1(p - 3) - 1(2.4 + 2p), we distribute the coefficient 1 to the terms inside the first parentheses and the coefficient -1 to the terms inside the second parentheses:

= p - 3 - (2.4 + 2p)

Next, we can remove the parentheses:

= p - 3 - 2.4 - 2p

Combining like terms:

= (p - 2p) - 3 - 2.4

= -p - 3 - 2.4

= -p - 5.4